Acceptability of Website-Based Learning Media within the Merdeka Learning Model among Teachers across West Java - Waryati Waryati; Yunus Abidin; Dede Tri Kurniawan (Journal of Future Education, 2024)
Entering the 21st century, technological developments are currently developing steadily. Entering the modern era which is marked by technological developments that continue to change every day, all aspects of life are now affected by advances in digital technology. Web-based learning media is a form of utilizing the latest technology in the educational context, which is implemented in the teaching and learning process using technology. Therefore, researchers will study and research the acceptability of Website-Based Learning Media with the Independent Teacher Learning Model throughout West Java to see the extent to which teachers have mastered the creation of digital-based learning media. This research uses a quantitative approach with correlational survey methods and path analysis. The research results show that Self E Self-Efficacy (Self Application) has a relationship with Behavioral Intention (Acceptance of technology). This can be seen from the p value which gets a value of 3.82 and the T Value with a value of 0.00 which exceeds the minimum and maximum limits set. determined, and it can be concluded that this variable is said to have a significant effect.